Further Evidence of Possible Therapeutic Uses of Sambucus nigra L. Extracts by the Assessment of the In Vitro and In Vivo Anti-Inflammatory Properties of Its PLGA and PCL-Based Nanoformulations - Ana Henriques Mota; Noélia Duarte; Ana Teresa Serra; António Ferreira; Maria Rosário Bronze; Luísa Custódio; Maria Manuela Gaspar; Sandra Simões; Patrícia Rijo; Lia Ascensão; Pedro Faísca; Ana Silveira Viana; et al. (MDPI AG, 2020)
Sambucus nigra L. is widely used in traditional medicine with different applications. However, confirmative studies are strongly required. This study aimed to assess the biological activities of the S. nigra flower's extract encapsulated into two different types of nanoparticles for optimizing its properties and producing further evidence of its potential therapeutic uses. Different nanoparticles (poly(lactide-co-glycolide, PLGA) and poly-Ɛ-caprolactone (PCL), both with oleic acid, were prepared by emulsification/solvent diffusion and solvent-displacement methods, respectively. Oleic acid was used as a capping agent. After the nanoparticles' preparation, they were characterized and the biological activities were studied in terms of collagenase, in vitro and in vivo anti-inflammatory, and in vitro cell viability. Rutin and naringenin were found to be the major phenolic compounds in the studied extract. The encapsulation efficiency was higher than 76% and revealed to have an impact on the release of the extract, mainly for the PLGA. Moreover, biochemical and histopathological analyses confirmed that the extract-loaded PLGA-based nanoparticles displayed the highest anti-inflammatory activity. In addition to supporting the previously reported evidence of potential therapeutic uses of S. nigra, these results could draw the pharmaceutical industry's interest to the novelty of the nanoproducts.